Túnez en la encrucijada geopolítica del Mediterráneo: migración, seguridad y la externalización fronteriza de la Unión Europea - Memmi, Emna (Journal of the Spanish Institute for Strategic Studies, 2025)
This article examines the migration flows from Tunisia to Europe following the Arab Spring, presenting a security dilemma for the European Union's foreign policy and its southern border states within the multipolar context that has emerged after a decade of uprisings. The research investigates how the multipolar environment and the anarchic structure of the international system influence European migration policy and the externalisation processes at its borders. Focusing specifically on North Africa, particularly Tunisia, the study investigates how the chaos generated in the aftermath of the events of 2011 has altered migration routes, thereby positioning Tunisia as a critical point of departure and transit within the Central Mediterranean migration pathways. This research offers a novel academic interpretation of migration phenomena in the Central Mediterranean, challenging the prevailing Eurocentric perspectives in contemporary discussions regarding European migration policy. It highlights the power asymmetry that exists between traditional European powers and their southern neighbours, advocating for a critical examination of approaches to address this security dilemma amidst increasing regional complexities and uncertainty.
Keywords: Migration Governance; EU Foreign Policy; Security Dilemma; Arab Spring; Multipolarity